Effects of Family Intervention on Physical Activity and Sedentary Behavior in Children Aged 2.5-12 Years: A Meta-Analysis - Ting Huang; Guanggao Zhao; Haoyuan Tan; Hua Wu; Jinmei Fu; Shunli Sun; Wendi Lv; Zihao He; Qiming Hu; Minghui Quan (Frontiers Media S.A., 2021)
Introduction: To use a quantitative approach to examine the effects of family interventions on physical activity (PA) and sedentary behavior (SB) in children aged 2. 5-12 years.Methods: PubMed, OVID, Web of Science, and others were searched from their inception to May 2020. Intervention studies that examined the effects of family interventions on PA among children aged 2.5-12 years were included in this meta-analysis. Lastly, subgroup analyses were conducted to examine the potential modifying effects of family intervention's characteristics and study quality.Results: Eleven articles met the inclusion criteria for this review. Studies investigated a range of PA outcomes, including moderate-to-vigorous PA (MVPA), total PA (TPA), daily steps, and SB levels. Meta-analysis showed that family intervention had a significant effect on PA [standardized mean difference (SMD) = 0.10; 95% CI = 0.01-0.19], especially for daily steps [weight means difference (WMD) = 1,006; 95% CI = 209-1,803], but not for SB (WMD = −0.38; 95% CI = −7.21-6.46). Subgroup analyses indicated the improvements in PA occurred when children were 6-12 years old, intervention focused on PA only, intervention duration ≤ 10 weeks, and "low risk of bias" study performed.Conclusions: Family intervention may be a promising way to promote children's PA levels, especially for daily steps.Trial Registration: Meta-analysis protocol was registered on PROSPERO: CRD42020193667.